Dukhovno-nravstvennye aspekty khudozhestvennogo vospitaniia detei i molodiozhi - Graf M. I. (Pedagogical Activity of an Educational Organization – The Space of Personal Growth of Participants in Educational Relations, 2022)
The article deals with the problem of educating and educating students of a children's art school in the context of the tasks of developing a harmonious creative personality with Russian traditional spiritual values. The purpose of this painstaking work is to develop special pedagogical conditions for involving students in classroom and extracurricular activities.The main forms and methods of organizing various types of activities in accordance with this issue are presented. Attracting children and youth to spiritual values ​​and maintaining their moral health through teaching the fine arts require professional competence, an active life position and indifference of teachers.
Keywords: информационные технологии; внеурочная деятельность; information technology; духовные ценности; чтение; изобразительное искусство; наблюдение; spiritual values; extracurricular activities; educational tasks; нравственное здоровье; воспитательные задачи; reading; visual arts; observation; moral health